ANALISIS PENGARUH NILAI TUKAR, PDB, SUKU BUNGA DAN THE FED RATE TERHADAP IDX FINANCE SEBELUM DAN SESUDAH MEREBAKNYA COVID-19 DI INDONESIA - Rafly Fauzan Hartadi (2023)
Economic fluctuations have an impact on a country's investment climate. This research was conducted to analyze the effect of the exchange rate, GDP, interest rates and The Fed Rate on IDX Finance before and after the outbreak of Covid-19 in Indonesia. This study examines the long-term and short-term effects of these variables using the ECM (Error Correction Model) test. The sample is used quarterly with an observation period of 2008-2022. The results of research conducted using the ECM method show that exchange rates have a significant effect on IDX Finance in the long and short term. The GDP variable has a significant effect in the long term and has no significant effect on IDX Finance in the short term. Meanwhile, the interest rate and the Fed rate variables have no significant effect on the long and short term. The Covid-19 pandemic in the long and short term has no significant impact on IDX Finance.